Socioeconomic status indicators, physical activity, and overweight/obesity in Brazilian children - Matsudo,Victor Keihan Rodrigues (2016)
Abstract Objective: To analyze the associations between socioeconomic status (SES) indicators and physical activity and overweight/obesity in children. Methods: 485 children wore accelerometers for 7 days. Variables included time in sedentary behavior and moderate-to-vigorous physical activity (MVPA), and steps/day. Children were further categorized as meeting or not meeting guidelines of ≥60min/day MVPA and ≥12,000 steps/day. Body mass index (BMI) and body fat percentage (BF%) were measured using bioelectrical impedance. Overweight/obesity was defined as BMI >+1 SD and BF% ≥85th percentile. Parents answered questionnaires that questioned total annual household income, parental education level, parental employment status and automobile ownership. Results: Children averaged 59.5min/day in MVPA (44.1% met MVPA guidelines), and 9639 steps/day (18.4% met steps/day guidelines). 45.4% and 33% were overweight/obese classified by BMI and BF% respectively. Higher relative total annual household income level (Odds Ratio 0.31; 95% confidence interval=0.15-0.65), and relatively higher maternal (OR=0.38; 95%CI=0.20-0.72) and paternal (OR=0.36; 95%CI=0.17-0.75) education levels were associated with lower odds of children meeting MVPA guidelines. Household automobile ownership was associated with lower odds of children meeting MVPA (OR=0.48; 95%CI=0.31-0.75) and steps/day guidelines (OR=0.44; 95%CI=0.26-0.74). Conclusions: SES indicators were not associated with overweight/obesity, but higher SES was associated with lower odds of children meeting MVPA guidelines.